Beyond coloniality : citizenship and freedom in the Caribbean int ellectual tradition - Kamugisha, Aaron; Indiana University. Press (Bloomington, Indiana : Indiana University Press, 2019)
Against the lethargy and despair of the contemporary Anglophone Cari bbean experience, Aaron Kamugisha gives a powerful argument for advanci ng Caribbean radical thought as an answer to the conundrums of the pres ent. Beyond Coloniality is an extended meditation on Caribbean thought and freedom at the beginning of the 21st century and a profound rejecti on of the postindependence social and political organization of the Ang lophone Caribbean and its contentment with neocolonial arrangements of power. Kamugisha provides a dazzling reading of two towering figures of the Caribbean intellectual tradition, C. L. R. James and Sylvia Wynter , and their quest for human freedom beyond coloniality. Ultimately, he urges the Caribbean to recall and reconsider the radicalism of its most distinguished 20th-century thinkers in order to imagine a future beyon d neocolonialism.
Beyond Caribbean coloniality -- Part I. The Coloniality of the prese nt -- The coloniality of citizenship in the contemporary Anglophone Car ibbean -- Creole discourse and racism in the Caribbean -- Part II. The Caribbean beyond -- A Jamesian Poiesis? C.L.R. James's new society and Caribbean freedom -- The Caribbean beyond: Sylvia Wynter's black experi ence of new world coloniality and the human after Western Man -- Conclu sion: A Caribbean sympathy.
Includes bibliographical references (p. 221 - 248) and index.
Keywords: Postcolonialism -- Caribbean Area -- History -- 21st century; Decolonization -- Caribbean Area -- History -- 21st century; Caribbean literature (English) -- 21st century -- History and critic ism; Caribbean Area -- Intellectual life -- History -- 21st century; Caribbean Area -- Politics and government -- History -- 21st century .